Histopathologic and Sonographic Analysis of Laparoscopic Removal Ovarian Nonendometriotic Cyst: The Evaluating Effects on Ovarian Reserve - Soheila Sarmadi; Farahnaz Sadat Ahmadi; Shahram Ejtemaei Mehr; Azizeh Ghaseminejad; Kazem Mohammad; Sepideh Nekuie; Soleiman Abbasi; Mehrdad Karimi; Fereshteh Gharibpoor; Zahra Elahipanah (Acta Medica Iranica, 2014)
Currently, laparoscopic cystectomy is the first-line therapy for ovarian benign cysts that are resistant to current therapies. There are different studies that point to ovarian reserve damage due to laparoscopic cystectomy. In this study, we evaluate the ovarian damage following laparoscopic cystectomy for non-endometriosis cysts using ultrasound and pathology findings. This is a prospective cohort study conducted between 7 rd month of 2011 and 10th month of 2012 in Women hospital affiliated to Tehran university of medical sciences.45 non-endometriosis cysts (17 teratoma,7 mucinous, 10 simple serous and 11 simple cysts) underwent laparoscopic cystectomy with stripping technique. Amount of excised parenchyma, number of lost oocytes and cyst wall fibrosis thickness were histopathologically studied. Before and 3 months after surgery antral follicle count was evaluated by ultrasound. AFC after cystectomy for teratoma and simple serous was significantly reduced P<0.05. By larger teratomas and more parenchyma inadvertently removed during their excision (1.64, 0.255) reduced AFC was seen and in simple serous cysts with more removed parenchyma amount (1.5) reduced AFC occurred. In our study simple cysts excision led to a loss in AFC that was not associated with any other cyst parameters. Mucinous cysts resection led to no specific ovarian reserve damage. Laparoscopic cystectomy for non-endometriosis leads to reduced ovarian reserve.